Social Competence Analysis of Science Teachers During the Covid-19 Pandemic - Azhar Azhar; Khaikal Ramadhan; Dedi Irawan (Jurnal Penelitian Pendidikan IPA, 2022)
The purpose of this study was to analyze the social competence of science teachers. It was conducted in 22 SMP Negeri Dumai City with a population of 86 science teachers in public junior high schools. The research sample was 71 science teachers calculated using the Slovin formula at an error rate of 0.05%. The instrument used in data collection was a questionnaire that was pre-tested to 30 science teachers (15 science teachers at SMPN Dumai City and 15 science teachers at SMPN Duri). From the 30 items of the questionnaire statement that were tested, the validity of each item was calculated with the product moment correlation with the help of the SPSS version 23, 29 valid items were obtained. Calculation of instrument reliability using the Cronbach Alpha formula was obtained 0.931 very reliable category. Furthermore, the social competence questionnaire instrument for science teachers who had met the validity and reliability requirements was used to collect data for the research sample of 71 science teachers at public junior high schools in the city of Dumai. The results of descriptive data analysis showed that the social competence of science teachers at the Dumai City Junior High School was 54.90% (39 science teachers) in the medium category, 25.30% (18 science teachers) who had high category competence and 19.70% (14 science teachers) out of 71 science teachers in the low category. Thus, the social competence of science teachers in Dumai City Junior High School is mostly in the medium category.